Handbook bibliometrics - Ball, Rafael (De Gruyter reference., 2021)
"Bibliometrics and altmetrics are increasingly becoming the focus of interest in the context of research evaluation. The Handbook Bibliometrics provides a comprehensive introduction to quantifying scientific output in addition to a historical derivation, individual indicators, institutions, application perspectives and data bases. Furthermore, application scenarios, training and qualification on bibliometrics and their implications are considered"--Publisher's website.